Development of Arabic Curriculum in Improving Pedagogic Competence of Lecturer Ma'had Umar Bin Al-Khattab - Ragilian Diasi Nira; Yayuk Fauziyah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The development of the Arabic language curriculum is the planning of Arabic language learning which includes the planning of the components of the objectives, content, strategies and evaluations to bring learners to the desired objectives of the Arabic language learning. Pedagogic competence of lecturers is the ability of lecturers in managing student learning which among the aspects is curriculum development. This research is qualitative research that aims to find out how the development of the Arabic curriculum in ma'had Umar bin Al-Khattab (MUBK) and how to achieve the development of the Arabic language curriculum in improving the pedagogic competence of lecturers. In the process, this research uses data collection techniques in the form of documentation, interviews and observations. The data obtained is analyzed by data reduction, data presentation and conclusion examination. It is known from the results of data and analysis that the development of the Arabic curriculum in (MUBK) following the opinion of Audrey Nicholls and Howard Nicholls affirmed by Michaelis, Grossman, and Scott. The achievement of the development of Arabic curriculum in ma'had Umar bin Al-Khattab can improve the pedagogical competence of lecturers in the aspect of curriculum refining. The increase was 87.5% in the making of RPS, 50% in making teaching plans at each meeting, 0% in teaching materials in order and teaching materials following the provisions set by 2.5%. If calculated, the improvement of pedagogic competence of lecturers in developing the curriculum by 35%.